Number 40 (May 2000) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2000)
(May 2000) - Survey of fishes in the southern tributaries of the South Bend of the Tennessee River with notes on Wheeler, Wilson, and Pickwick Reservoirs. By E.B. Dale Jones III William Bartram's early observation of a nest association between cyprinid fishes. By Philip A. Cochran.
Keywords: fishes; tennessee river; crprinid fishes